Developing the Test Items Based on High Order Thinking Skills in Chemical Equilibrium Materials Using Rasch Model - Ariyani, Ade; Dibyantini, Ratu Evina; Darmana, Ayi (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Development the Test Items Based on High Order Thinking Skills in Chemical Equilibrium Materials Using Rasch Model. Objectives:This study aims to develop HOTS (High Order Thinking Skill) based items on chemical equilibrium material using the Rasch model. Methods: The type of research used is research and development through the ADDIE model. Respondents in the study were 25 students of class XII at the Superior High School in North Sumatra, distinguished by gender and grade X. Findings: The test items developed consisted of 10 questions that had gone through the validation stage by experts and then tested and analyzed using the Winsteps software. Conclusion: Content validation obtained 100% fit indexed items; the reliability of the person category is sufficient and the item is in the good category with Cronbach α=0.72 (good); the value of separation person (1.27) is in the weak category and item (2.49) is in the good category; Item difficulty levels are sorted from very easy: medium: difficult: very difficult. Respondents with codes 02LO and 24LO (logit +4.36) are respondents with the highest ability, codes 18PR and 19PR (logit -1.97) are respondents with the lowest ability. Guttman Matrix Scalogram, two respondents have the potential to guess the answer and four respondents have the potential to commit fraud.Keywords: HOTS Items, Chemical Equilibrium, Rasch Model.DOI : 10.23960/jppk.v13.i1.2024.01